Expression Profile of New Gene Markers Involved in Differentiation of Canine Adipose-Derived Stem Cells into Chondrocytes - Jankowski, Maurycy; Kaczmarek, Mariusz; Wąsiatycz, Grzegorz; Konwerska, Aneta; Dompe, Claudia; Bukowska, Dorota; Antosik, Paweł; Mozdziak, Paul; Kempisty, Bartosz (Genes, 2022)
The interest in stem cell research continuously increased over the last decades, becoming one of the most important trends in the 21st century medicine. Stem cell-based therapies have a potential to become a solution for a range of currently untreatable diseases, such as spinal cord injuries, type I diabetes, Parkinson's disease, heart disease, stroke, and osteoarthritis. Hence, this study, based on canine material, aims to investigate the molecular basis of adipose-derived stem cell (ASC) differentiation into chondrocytes, to serve as a transcriptomic reference for further research aiming to introduce ASC into treatment of bone and cartilage related diseases, such as osteoarthritis in veterinary medicine. Adipose tissue samples were harvested from a canine specimen subjected to a routine ovariohysterecromy procedure at an associated veterinary clinic. The material was treated for ASC isolation and chondrogenic differentiation. RNA samples were isolated at day 1 of culture, day 30 of culture in unsupplemented culture media, and day 30 of culture in chondrogenic differentiation media. The resulting RNA was analyzed using RNAseq assays, with the results validated by RT-qPCR. Between differentiated chondrocytes, early and late cultures, most up- and down-regulated genes in each comparison were selected for further analysis., there are several genes (e.g., MMP12, MPEG1, CHI3L1, and CD36) that could be identified as new markers of chondrogenesis and the influence of long-term culture conditions on ASCs. The results of the study prove the usefulness of the in vitro culture model, providing further molecular insight into the processes associated with ASC culture and differentiation. Furthermore, the knowledge obtained could be used as a molecular reference for future in vivo and clinical studies.
Keywords: Genetic Markers; Chondrocytes; chondrocytes; Osteoarthritis; psi; Dogs; differentiation; RNAseq; chondrocyty; osteoartróza; RNA; Animals; zvířata; matrixová metaloproteinasa 12; Adipose Tissue; kultivační média; Stem Cells; adipose; kmenové buňky; transcriptomics; genetické markery; stem cells; tuková tkáň; Matrix Metalloproteinase 12; Culture Media